Making Sense of Word Reading Difficulties: Principles of Clinical Assessment - Zipoli, Richard P. (Communication Disorders Quarterly, 2022)
Speech-language pathologists (SLPs) are increasingly called upon to help assess students with word-recognition difficulties, including dyslexia. Although SLPs tend to have comparatively strong knowledge regarding the phonological awareness skills that support word reading, findings from survey research indicate that many SLPs report limited knowledge and training on word recognition and phonics. The purpose of this article is to provide a systematic framework for assessing and interpreting students’ word reading skills. Five potential components of word reading assessment will be examined: word recognition, phonological decoding, automaticity, performance with specific phonics patterns, and reading multimorphemic and multisyllabic words. Emphasis will be given to how specific test formats and procedures can be used to help identify patterns of word reading difficulty.
Keywords: assessment; automaticity; decoding; dept.cmd; peer-reviewed; phonics; reading; word recognition